Respostas
respondido por:
9
Ola Roberto
2x + 3y = -2
2x - 3y = 4
adição
4x = 2
x = 2/4 = 1/2
1 - 3y = 4
3y = 1 - 4 = -3
y = -1
2x + 3y = -2
2x - 3y = 4
adição
4x = 2
x = 2/4 = 1/2
1 - 3y = 4
3y = 1 - 4 = -3
y = -1
respondido por:
4
2x + 3y = - 2
2x - 3y = 4 (+)
-----------------------
4x = 2
x = 2 (:2)
-----
4 (:2)
x = 1
-----
2
2x + 3y = - 2
2. 1 + 3y = - 2
----
2
1 + 3y = - 2
3y = - 2 - 1
3y = - 3
y = - 3/3
y = - 1
2x - 3y = 4 (+)
-----------------------
4x = 2
x = 2 (:2)
-----
4 (:2)
x = 1
-----
2
2x + 3y = - 2
2. 1 + 3y = - 2
----
2
1 + 3y = - 2
3y = - 2 - 1
3y = - 3
y = - 3/3
y = - 1
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás